KETAHANAN PANGAN DI KOTA PAGARALAM, PROVINSI SUMATERA SELATAN TAHUN 2001—2010 - Frema Apdita; Yayuk Farida Baliwati (Food and Nutrition Society of Indonesia, 2012)
ABSTRACTThis study aim to analyze the food resouces in Pagaralam District, South Sumatera Province in 2001—2010. The study design was retrospective with secondary data analysis covering policies, budgeting, food production, exports, imports and number of population. Data processing included analysis for production, exports, imports, food availability and food suffiency by trend, line, ratio availability and ratio of imports. Food availability policy and food availability budgeting were analyzed using content analysis. The results indicate increasing of production on some commodities but supply doesn’t fulfill the demand. Food availability increases and energy adequacy has already reached the Minimum Services Standard (90%), but not for intake protein. Desirable Dietary Pattern (DDP) score is still below 90. The food availability policy and budget do not support the General Policy for Food Security 2006—2010 and still focused on water resources management.Key words: energy and protein adequacy, food availabilityABSTRAKPenelitian ini bertujuan untuk menganalisis sumberdaya pangan di Kota Pagaralam Provinsi Sumatera Selatan tahun 2001—2010. Data sekunder terdiri dari kebijakan anggaran, produksi pangan, ekspor dan impor pangan serta jumlah penduduk. Desain penelitian ini adalah retrospektif menggunakan data sekunder. Pengolahan data dimulai dengan menganalisis produksi, ekspor dan impor, ketersediaan pangan dan kecukupan pangan menggunakan analisis tren, analisis garis, analisis rasio ketersediaan dan analisis rasio impor. Kebijakan dan anggaran ketersediaan pangan dianalisis menggunakan analisis isi. Peningkatan produksi beberapa komoditi namun produksi belum mencukupi kebutuhan. Ketersediaan pangan mengalami peningkatan dan kecukupan energi sudah mencapai SPM (90%), akan tetapi kecukupan protein masih defisit. Skor PPH masih di bawah 90. Kebijakan dan anggaran belum sepenuhnya sesuai dengan Kebijakan Umum Ketahanan Pangan (KUKP) 2006—2010 dan masih terfokus pada sektor pengelolaan sumberdaya air.Kata kunci: kecukupan energi dan protein, ketersediaan pangan